2022
DOI: 10.3390/resources11120116
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Rice Yield Assessment in Central Kalimantan, Indonesia, under Different Cultural Practices

Abstract: This research aimed to assess the performance of a technology package in relation to rice yield in a B-type tidal rice field in Central Kalimantan province (Indonesia). We selected four areas with different hydrological conditions, soil characteristics, and farmer management systems in Pulangpisau and Kapuas Regency. The introduced technology package covered water management, soil tillage, amelioration and fertilization, adaptive high-yielding varieties, and crop protection. The results showed that, on average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, the exchangeable Mg content was categorized as high. These results are consistent with previous studies (13). Generally, soils in tidal swamp areas are deficient in major elements that determine rice productivity improvement.…”
Section: Soil Characteristicssupporting
confidence: 93%
“…However, the exchangeable Mg content was categorized as high. These results are consistent with previous studies (13). Generally, soils in tidal swamp areas are deficient in major elements that determine rice productivity improvement.…”
Section: Soil Characteristicssupporting
confidence: 93%
“…Schedule for the cultivation of local and superior varieties of rice in South Kalimantan province. Reused with permission from [66]; copyright owned by the MDPI.…”
Section: Farming Systems and Technology Adoptionmentioning
confidence: 99%
“…The dolomite treatment was significantly different from without dolomite treatment on the parameters of rice yield components. Control treatment showed that the plants could not grow properly and were unable to produce panicles and grain [12,13]. The application of micronutrient fertilizers affected shoot weight at a dose of 4 g L -1 .…”
Section: Rice Yieldmentioning
confidence: 99%